A systemic response to supporting frontline inpatient mental health staff in coping with the COVID-19 outbreak. Issue 1 (12th November 2020) - Cotter, Padraig; Jhumat, Nicola; Garcha, Eshia; Papasileka, Eirini; Parker, Jennifer; Mupfupi, Ishmael; Currie, Ian
Abstract : Purpose: This paper aims to outline the process of supporting frontline inpatient mental health staff in developing ways of coping with COVID-19. Design/methodology/approach: A whole system approach was used in formulating and developing support structures with particular focus on relationship-focused coping. Findings: Interventions were developed to support staff in coping with problem-focused (e.g. systemic changes) and emotion-focused challenges (e.g. deaths of colleagues). These included psychoeducation, mindfulness-based meditation and rituals to mark the deaths of colleagues. Staff SPACE (Stopping to Process and Consider Events) sessions were used to support staff in managing the many emotions they were experiencing. Positive psychology-based interventions were used to keep morale up and help people to stay motivated. The process of seeking feedback and making changes was introduced to support staff in feeling heard and having a voice. The maternal or master intervention within each of the above was the relational component. Practical implications: This work aimed to boost the emotional and psychological literacy of the system. This will be important in the aftermath of the pandemic and could have many benefits thereafter. Social implications: The post-COVID-19 health-care workforce will experience significant challenges in terms of readjustment and recovery. It is important that appropriate measures are put in place to ameliorate this. Originality/value: An innovative systemic formulation of the impact of COVID-19 on frontline staff, and a coordinated way of dealing with this, is outlined.